Microstructure-Based Mechanical Model of Metal-Matrix Composite Materials and Coatings; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Balokhonov R. R.; Romanova V. A.; Schwab E. A.; Bakeev R. A.; Kulkov A. S.; Kulkov S. N. Sergey Nikolaevich (2018, 2018)
Title screen